Keadilan Sosial dalam Perspektif Pancasila: Analisis Filsafat Hukum Indonesia - Happy Sturaya Quratuainniza; Irwan Triadi (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
This research investigates the notion of sosial justice through the lens of Pancasila as the philosophical cornerstone of Indonesia’s legal framework. In contrast to earlier normative studies that predominantly emphasize the regulatory dimension of justice, this paper underscores Pancasila’s transformative capacity to embed moral, ethical, and societal values within the national legal structure. Employing a normative juridical approach, the study examines pertinent legal norms, prinsiples, and doctrines related to social justice, along with their manifestations in Indonesia’s legal practies. The results demonstrate that Pancasila, as teh ideological foundation of the state, offers a profound moral and philosophical grounding for establishing equitable and human-oriented legislation, nonetheless, its practical application remains impeded by an overly formalistic legal culture, insufficient internalization of values among legal practitioners, and ongoing structural inequalities. The originalitu of this study lies in its analytical reconstruction of Pancasila based legal philosophy as a normative paradgm designed to realize substantive justice and to reintroduce moral reasong into Indonesia’s legal development. Consequenty, this work contributes to the scholarly discourse on the incorporation of philosophical prinsiples into national legal reform and legal education, with the ultimate aim of reinforcing justice and human dignity within Indonesia’s legal order.